(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
The 21st century has presented humanity with new demands, opportunities, and challenges. Global crises, climate change, military conflicts, and technological revolutions necessitate a profound shift in human consciousness and worldview. In these circumstances, education and upbringing emerge as a key force in the development of both society and the individual. The ancient cultural heritage of the Kyrgyz people, its epic world, deep philosophical approach to life, and careful attitude towards nature demonstrate the immense influence of education and upbringing on the formation of human consciousness. This article provides a scientific analysis of the significance of education and upbringing in the modern world for the transformation of human consciousness and the betterment of the world.